FFAR2‐FFAR3 receptor heteromerization modulates short‐chain fatty acid sensing. Issue 1 (7th September 2017) - Ang, Zhiwei; Xiong, Ding; Wu, Min; Ding, Jeak Ling
Abstract : Free fatty acid receptors 2 and 3 (FFAR2/FFA2/GPR43 and FFAR3/FFA3/GPR41) are mammalian receptors for gut microbiota‐derived short‐chain fatty acids (SCFAs). These receptors are promising drug targets for obesity, colitis, colon cancer, asthma, and arthritis. Here, we demonstrate that FFAR2 and FFAR3 interact to form a heteromer in primary human monocytes and macrophages via proximity ligation assay, and during heterologous expression in HEK293 cells via bimolecular fluorescence complementation and fluorescence resonance energy transfer. The FFAR2‐FFAR3 heteromer displayed enhanced cytosolic Ca 2 + signaling (1.5‐fold increase relative to homomeric FFAR2) and β‐arrestin‐2 recruitment (30‐fold increase relative to homomeric FFAR3). The enhanced heteromer signaling was attenuated by FFAR2 antagonism (CATPB), Gαq inhibition (YM254890), or Gαi inhibition (pertussis toxin). Unlike homomeric FFAR2/ 3, the heteromer lacked the ability to inhibit cAMP production but gained the ability to induce p38 phosphorylation in HEK293 and inflammatory monocytes via a CATPB‐ and YM254890‐sensitive mechanism. Our data, taken together, reveal that FFAR2 and FFAR3 may interact to form a receptor heteromer with signaling that is distinct from the parent homomers—a novel pathway for drug targeting.—Ang, Z., Xiong, D., Wu, M., Ding, J. L. FFAR2‐FFAR3 receptor heteromerization modulates short‐chain fatty acid sensing. FASEB J. 32, 289‐303 (2018). www.fasebj.org